2018
DOI: 10.1177/0363546518755754
|View full text |Cite
|
Sign up to set email alerts
|

Meniscus Root Repair vs Meniscectomy or Nonoperative Management to Prevent Knee Osteoarthritis After Medial Meniscus Root Tears: Clinical and Economic Effectiveness

Abstract: Repair of medial meniscus root tears, as compared with total meniscectomy and nonsurgical treatment, leads to less osteoarthritis and is a cost-saving intervention. While small confirmatory randomized clinical head-to-head trials are warranted, the presented evidence seems to point relatively clearly toward adopting meniscus repair as the preferred initial intervention for medial meniscus root tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
195
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(202 citation statements)
references
References 29 publications
4
195
0
3
Order By: Relevance
“…Another work compared an in-situ suture anchor repair and a transtibial technique with sutures tied over a titanium plate in a porcine model 10 In the transtibial pullout repair, the mean permanent displacement registered after 1000 cycles of a [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] N load was 2.2 mm with the transtibial technique. Again, notorious methodological dissimilarities difficult contrast of the result with our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another work compared an in-situ suture anchor repair and a transtibial technique with sutures tied over a titanium plate in a porcine model 10 In the transtibial pullout repair, the mean permanent displacement registered after 1000 cycles of a [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] N load was 2.2 mm with the transtibial technique. Again, notorious methodological dissimilarities difficult contrast of the result with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical studies confirmed the importance of meniscal root integrity to preserve joint contact load distribution [1][2][3][4] and stability 5 . Meniscal root repair surgery aims to re-establish these meniscal functions 6,7 and to minimize progression of osteoarthritis 8 .…”
Section: Initial Biomechanical Properties Of Transtibial Meniscal Roomentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Recently, an international consensus statement was made that emphasized the greater effectiveness of the meniscal root repair over meniscectomy and conservative treatments. 5,6 In my opinion, the study by Jiang, Everhart, Abouljoud, Kirven, Magnussen, Kae, and Flanigan 7 entitled "Biomechanical Properties of Posterior Meniscal Root Repairs: Systematic Review" provides excellent insight for clinicians to determine the appropriate surgical technique for MMPRTs. The authors systematically reviewed the literature for the biomechanical properties of several meniscal root repair techniques: the fixation method (transtibial pullout repair and suture anchor repair), the configuration and material of the suture used in transtibial pullout repair, and the location of fixation (anatomic vs nonanatomic).…”
Section: See Related Article On Page 2189mentioning
confidence: 99%
“…For knee OA, a large number of neutrophils and oxidative stress metabolites are locally induced, which can enhance damage and degeneration of the meniscus [4]. The meniscus plays an irreplaceable role in lubricating joints and maintaining the bio-mechanical properties of the knee joints, and so chronic degeneration is also an important cause of knee OA [5,6,7].…”
Section: Introductionmentioning
confidence: 99%